Hubungan Durasi Duduk dan Faktor yang Berpengaruh terhadap Kejadian Low Back Pain pada Mahasiswa Fakultas Kedokteran Universitas Tarumanagara Angkatan 2020 - Khoirun Nikmah; Lamhot Asnir Lumbantobing (Jurnal Syntax Admiration, 2025)
Low Back Pain (LBP) is a pain of discomfort sensation, localized in the lower part of the cost and the lower folds of the gluteal and can radiate towards the legs to the feet. Medical students are at high risk of the occurrence of LBP one of the factors is the large number of busy lecture schedules that result in students doing static work that is sitting for long duration, so that many of the students are in the wrong sitting position, and this results in musculoskeletal complaints such as LBP. This research aimed to determine the relationship between the incidence of LBP in students and the duration of sitting and the factors that influence it. The design of this study is cross-sectional analytics, with the research respondents being students of the Faculty of Medicine, Tarumanagara University class of 2020. Subjects were taken using a consecutive sampling technique. LBP data collection using ODI and VAS questionnaires. The data were analyzed using a statistical program with a limit of meaning of p-values <0.05. The total respondents to this study were 127 students with an average age 19. A total of 89 (70.1%) respondents were female, 101 (79.5%) respondents had a sitting duration of ≥4 hours. The results of the analysis found that there was a meaningful relationship between the incidence of LBP in students and the duration of sitting during lectures with meaningful values (p=<0,01;PRR=1,578), meaningful results between sitting position (p=0.001), not/rare exercise frequency (P=0.349) and exercise duration never/<30 minutes (P=0.124), the result was not meaningful between BMI and LBP (p=0.995;PRR=1.003). Based on epidemiological analysis, the factor that most affects LBP in students of the Faculty of Medicine, Tarumanagara University class of 2020 is wrong sitting position (PRR= 6.029), exercise frequency not/rare (PRR=2.692), with exercise duration never/<30 minutes (P=0.124).